Assessing continuing education practices and preferences amongst Lebanese hospital pharmacists - Iskandar, Katia (2018)
Background: Continuing education (CE) is an international tool that requires lifelong active participation in learning activities allowing the pharmacist to stay a major player among others. In 2014 the CE program was introduced to the pharmacists licensed in Lebanon as a mandatory requirement for re-licensure. In the absence of guidelines regarding the quality and quantity of CE programs, behavioral resistance to precipitate in the CE programs might be encountered among the pharmacists. Objective: The objective of this study is to assess the perceptions of pharmacists working in Lebanese hospitals on the continuing education preferences. The advantage of this program is to collect information that would help the Order of Pharmacy in Lebanon to upgrade the CE program in a way that is more acceptable and convenient for the pharmacists. Methods: A cross-sectional study was carried out in 2016, using a proportionate random sample of Lebanese hospital pharmacies from all governorates in Lebanon. A structured questionnaire was distributed to all hospital pharmacies in Lebanon. Descriptive statistics were calculated for all study variables. This includes the mean and standard deviation for continuous measures, counts and percentages for categorical variables Results: A total of 107 (53.5%) participants completed the questionnaires. The majority of participants were from Beirut and Mount Lebanon. The percentage of participants working at private hospitals was (68.2%).The majority of participants who completed the questionnaire (86.2%) agreed that continuing education programs affects their way of practice and increases their knowledge. Their preferred CE types to be used in the future were the computer based ones (60.6%), interactive workshops (45.5%) and printed materials (44.9%). Their considerations for selecting the CE type is based on their interest in the topic (80.6%), the ease of access to print or online material (77.2%), or the convenience of being offered during an event (67.1%). Participants noted that barriers to attend live CEs were mainly work responsibilities (76%), travel distance (65.6%), family commitments (48.4%) and scheduling (40.6%). Conclusions: Lebanese hospital pharmacists are highly committed to CE. They consider it a practical tool for career development and advancement.